Treatment of Long Bone Fractures in Calves with Ilizarov External Fixator - Gülaydin, Ali; Sarierler, Murat (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
In this study, the advantages and disadvantages of Ilizarov external fixator in the treatment of long bone fractures in calves were investigated. For this purpose, 26 calves of different breeds, ages and genders, having metacarpal (n = 12), metatarsal (n = 5) and antebrachial (n = 9) fractures underwent surgery under general anaesthesia. Frames, which were prepared before surgery in accordance with the radiographic findings, were applied under open reduction in 18 cases, and under closed reduction in eight cases. In the postoperative period, all calves except one started to bear some weigh on the injured limb on the first day, while the remaining calf did the same on the second day. The consolidation started in the first 2 weeks for 24 of the calves and was completed by the day 55. In the two remaining cases, it started in the third week and was completed on day 71 and day 90, respectively.The soft tissue wounds were completely healed in all calves and no complications occurred. In five calves that were not kept in our clinic pin tract infections formed. They were controlled rapidly, and there was no change in the fracture reduction or healing duration.In conclusion, in our study, the Ilizarov external fixator system was applied to long bone fractures in cattle calves, in cases where the fragments were not large enough to apply pins and plates, and which became open and infected after defective bandage practices or unsuitable treatment. Fractures completely healed in all cases, without any complications. These results show that many of the long bone fractures experienced by calves, that were considered for amputation due to the anticipated inability to treat them successfully, could be treated with the use of the Ilizarov system.
Keywords: calf; fracture; Ilizarov; long bone